1992
DOI: 10.1002/gcc.2870050106
|View full text |Cite
|
Sign up to set email alerts
|

Pleomorphic adenoma cells vary in their susceptibility to SV40 transformation depending on the initial karyotype

Abstract: Chromosomal aberrations involving 8q12 or 12q13-15 characterize two cytogenetic subgroups of salivary gland pleomorphic adenomas. As the tumors of the two groups differ in their clinical and histologic characteristics, we decided to determine their susceptibility to SV40 transformation. We transfected cell cultures from 13 adenomas with aberrations involving 8q12 and from seven adenomas with involvement of 12q13-15 using an SV40 plasmid coding for the early region of the viral genome. Whereas all cultures with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

1994
1994
1999
1999

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…The lack of apparent association between LOH on 8q in tumors with malignant conversion in PA suggests that this is an early event in the progression of these tumors. This finding correlates well with the study of Kazmierczak et al, 15 which showed that all primary cultures of PA with a 12q13‐15 arrangement were susceptible to SV40 transformation (7 of 7), whereas those specimens with 8q12 abnormalities were less likely to undergo transformation (4 of 13). Our specimen with CXPA showed LOH at both 8q and 12q loci.…”
Section: Discussionsupporting
confidence: 91%
“…The lack of apparent association between LOH on 8q in tumors with malignant conversion in PA suggests that this is an early event in the progression of these tumors. This finding correlates well with the study of Kazmierczak et al, 15 which showed that all primary cultures of PA with a 12q13‐15 arrangement were susceptible to SV40 transformation (7 of 7), whereas those specimens with 8q12 abnormalities were less likely to undergo transformation (4 of 13). Our specimen with CXPA showed LOH at both 8q and 12q loci.…”
Section: Discussionsupporting
confidence: 91%
“…Intensive efforts have been made in the past to establish salivary gland tumor cell lines, but they have achieved only a low rate of success (Fujioka et al ., 1996; Kazmierczak et al ., 1992). Here, we have described the establishment and characterization of 9 cell lines derived from 9 salivary gland tumor cell cultures by infection with the HPV16 E6 and E7 genes.…”
Section: Discussionmentioning
confidence: 99%
“…In cases where structural changes have been observed, they frequently are reciprocal translocations in benign tumors or 6q deletions in malignant tumors (Sandros et al ., 1990). By contrast, the few salivary gland tumor cell lines established to date have complex karyotypic abnormalities (Bullerdiek et al ., 1990; Fujioka et al ., 1996; Kazmierczak et al ., 1992). The high frequency of normal karyotypes seen in salivary gland tumors raises the question of whether these cells represent bona fide tumor cells without gross chromosomal deviations or are actually contaminating stromal cells or normal salivary gland epithelial cells (Sandros et al ., 1990).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This event has to some extent been mitigated, albeit not completely eliminated, by the use of hTERT as a cotransforming gene [137,[183][184][185][186]. Because there are numerous genetic changes that need to occur to result in immortalization [41, 66,183,[187][188][189][190], it is important that the cells are grown for extended periods (generally >150-200 generations) to ascertain whether they are in fact immortalized. Once the cells have gone through a crisis event, it will be important to reevaluate them in the context of the desired phenotypic endpoints.…”
Section: Discussionmentioning
confidence: 99%